2018
DOI: 10.1097/corr.0000000000000535
|View full text |Cite
|
Sign up to set email alerts
|

MRI of THA Correlates With Implant Wear and Tissue Reactions: A Cross-sectional Study

Abstract: Background MRI is predictive of adverse local tissue reactions (ALTRs) after THA but how MRI directly relates to implant surface wear, fretting, and trunnion corrosion at different articulations between implant components remains unclear. MRI generates high-contrast images to display soft tissues around arthroplasty and may provide a One of the authors certifies that she (HGP), or a member of her family, has received or may receive payments or benefits, during the study period, an amount of more than USD 1,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 55 publications
2
53
0
Order By: Relevance
“…25 These findings are analogous to the literature regarding the diagnostic properties of MRI for diagnosing liner wear in total hip arthroplasty. 41 In clinical practice, early loosening is very difficult to diagnose on X-ray, and diagnosis usually becomes clearer only upon follow-up X-rays. 42 When X-ray is inconclusive, other imaging modalities may be used, 42 and based on these results, MRI may be considered as a possible modality.…”
Section: Discussionmentioning
confidence: 99%
“…25 These findings are analogous to the literature regarding the diagnostic properties of MRI for diagnosing liner wear in total hip arthroplasty. 41 In clinical practice, early loosening is very difficult to diagnose on X-ray, and diagnosis usually becomes clearer only upon follow-up X-rays. 42 When X-ray is inconclusive, other imaging modalities may be used, 42 and based on these results, MRI may be considered as a possible modality.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large cohort retrieval study found correlations between MRI measurement of synovial thickness with severity of fretting and corrosion damage of the female head‐neck trunnion of femoral stems in modular designs ( ρ = 0.26; P = .015) and severity of ALTR on MRI with volumetric wear in metal‐on‐metal (MoM) bearings ( ρ = 0.93; P < .001) 17 . Synovial thickness has been indicated as a primary metric to evaluate the presence of an ALTR 32,34 …”
Section: Evaluating Synovial Reactionsmentioning
confidence: 99%
“…While MRI has been applied extensively to evaluate synovial reactions to metal‐on‐metal bearing constructs, it is equally applicable to metal‐on‐polyethylene constructs. A recent analysis found that metal‐on‐polyethylene hips demonstrated a distinct polymeric synovial response on MRI, whereas metal‐on‐metal bearing surfaces (hip resurfacing arthroplasty and metal‐on‐metal total joint replacement) and dual modular hips more commonly demonstrated ALTR 17 . Hips classified as having a polymeric synovial response on MRI had a greater number of particles present in tissue samples obtained during revision surgery.…”
Section: Evaluating Synovial Reactionsmentioning
confidence: 99%
“…The number of arthroplasty procedures performed to alleviate pain and improve function from chronic joint disorders continues to increase at a rapid rate, which has led to a correlative increase in subsequent revision surgery . The inherent soft tissue contrast of magnetic resonance imaging (MRI) makes it the most suitable imaging technique to assess postoperative joint integrity in arthroplasty cases . Metal induced susceptibility artifacts, however, make it difficult to image near such hardware .…”
Section: Introductionmentioning
confidence: 99%
“…1 The inherent soft tissue contrast of magnetic resonance imaging (MRI) makes it the most suitable imaging technique to assess postoperative joint integrity in arthroplasty cases. [2][3][4] Metal induced susceptibility artifacts, however, make it difficult to image near such hardware. 5,6 Though two-dimensional fast/turbo spin echo techniques acquired with small voxels and with higher readout encoding bandwidths can reduce artifacts, diagnostic capabilities near implants are still often compromised.…”
Section: Introductionmentioning
confidence: 99%